Implementation of e-commerce in improving the competitiveness of vocational secondary education student entrepreneurship products - Sintha Wahjusaputri; Tashia Indah Nastiti (Intelektual Pustaka Media Utama, 2022)
This study aimed to identify problems, describe, analyze, and evaluate the use of e-commerce to increase the competitiveness of innovative and entrepreneurial products produced by students of State Vocational High School 3 South Tangerang, Banten province. This research had three main stages, namely the preparation stage, the implementation stage, and the evaluation stage. The research location was the State Vocational High School 3 South Tangerang, Banten province, Indonesia, due to the school being outstanding in the field of Motorcycle and Animation expertise. The resource persons and respondents in this study were teaching teachers and students in classes 10-12 majoring in culinary, automotive, and animation. Implementing e-commerce activities at the production unit of State Vocational High School 3 South Tangerang, has increased the image of the production unit of State Vocational High School 3 South Tangerang. This study was a descriptive qualitative with the questionnaire, interview, and practice method. This study revealed that the application of e-commerce using the Shopee seller marketplace provided significant benefits and impacts for the production unit of State Vocational High School 3 South Tangerang. When the production unit implemented e-commerce, sales turnover increases rapidly, and the number of consumers, as a means of promotion, ease of transaction did not need to meet directly with buyers and can expand the business. However, there were also several obstacles, like weak human resources, intense competition, and the emergence of plagiarism of ideas and products.